2021
DOI: 10.1029/2020pa004072
|View full text |Cite
|
Sign up to set email alerts
|

Speleothem‐Based Hydroclimate Reconstructions During the Penultimate Deglaciation in Northern China

Abstract: Hydroclimatic change has a substantial impact on the lives and well-being of humans, especially in densely populated regions (Yang et al., 2015). As recorded in historical literature and as is known through modern observations, floods and droughts have occurred frequently in China, affecting not only agricultural production and regional economies, but also water security in China. Understanding the past variability of hydroclimatic change and its dynamics is essential for projecting future changes and mitigati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Factors influencing X/Ca ratios in speleothems are diverse, including hydrological processes (e.g., WRI, PAP/PCP), temperature, and speleothem growth rate, among others (Treble et al, 2003; Fairchild and Treble, 2009; Tan et al, 2014; Xue et al, 2021). In previous studies, trace elements varying positively in tandem with δ 13 C were suggested to be caused by rainfall-related hydrological processes (Cheng et al, 2016b; Tan et al, 2020b; Xue et al, 2021). Specifically, under dry climate conditions, prolonged WRI could increase the dissolution of bedrock.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Factors influencing X/Ca ratios in speleothems are diverse, including hydrological processes (e.g., WRI, PAP/PCP), temperature, and speleothem growth rate, among others (Treble et al, 2003; Fairchild and Treble, 2009; Tan et al, 2014; Xue et al, 2021). In previous studies, trace elements varying positively in tandem with δ 13 C were suggested to be caused by rainfall-related hydrological processes (Cheng et al, 2016b; Tan et al, 2020b; Xue et al, 2021). Specifically, under dry climate conditions, prolonged WRI could increase the dissolution of bedrock.…”
Section: Discussionmentioning
confidence: 99%
“…Although several speleothem records are available from central and southern China, for example, from the Sanbao (Dong et al, 2010; Cheng et al, 2016a), Lianhua (LH) (Cosford et al, 2008; H. Zhang et al, 2013), and Dongge (DG) Caves (Yuan et al, 2004; Wang et al, 2005), the climatic significance of these stalagmite δ 18 O records is highly debated and subject to multiple interpretations (e.g., moisture sources and pathways, upstream rainout, and regional rainfall) (Yuan et al, 2004; Maher and Thompson, 2012; Tan et al, 2018a). The δ 13 C and trace elements ratios (e.g., Sr/Ca, Mg/Ca, and Ba/Ca) in stalagmites, which reflect the local hydrological environment (Fairchild and Treble, 2009; Xue et al, 2021; Zhang et al, 2021), are thus better suited to reconstruct the local rainfall variability. In this study, we present a suite of stalagmite-based stable isotope (δ 18 O, δ 13 C) and trace element records (Sr/Ca, Mg/Ca, Ba/Ca) from Remi Cave, Hunan Province, aiming to reconstruct the monsoon precipitation variations in south-central China across the 4.2 ka event.…”
Section: Introductionmentioning
confidence: 99%
“…The interpretation of speleothem δ 13 C Speleothem δ 13 C has often been linked to various factors, including the type of vegetation (i.e. C 3 vs C 4 ) above the cave, which determine the δ 13 C of soil CO 2 , biomass, which affects the soil CO 2 concentration, biological activities in the soil, carbon component dissolved from the host rock and prior carbonate precipitation (PCP) in the epikarst and within the cave (McDermott, 2004;Genty et al, 2006;Ridley et al, 2015;Lechleitner et al, 2017;Fohlmeister et al, 2020;Xue et al, 2021). In northern China, precipitation is the dominant factor affecting vegetation density and/or types and then plays an important role in causing changes in the speleothem δ 13 C record (Li et al, 2020).…”
Section: Discussionmentioning
confidence: 99%